Reduction of Typical Diesel NOx Emissions by SCR-NH3 Using Metal-Exchanged Natural Zeolite and SBA-15 Catalysts. - Alcantara, P.M.P.; Moura de Oliveira, Mona Lisa; Santiago de Araújo, Jesuína Cássia; Dos Santos Araújo, Rinaldo; Chaves de Lima, Rita Karolinny; Bueno, André Valente; Vieira da Silva, Maria Eugênia; Costa Rocha, Paulo Alexandre; Rodríguez-Castellón, Enrique (MDPI, 2023)
In this work, the catalytic performance of clinoptilolite (CLIN) and SBA-15 catalysts, doped with Fe and Cu, was evaluated in the selective catalytic reduction of NO using NH3 as a reducing agent (SCR-NH3). Both Cu-CLIN and Fe-CLIN were obtained by ion-exchange using natural clinoptilolite zeolite originating from the Hrabovec deposit (northeast Slovakia region). Cu- SBA-15 and Fe-SBA-15 were prepared by impregnation into SBA-15 mesoporous synthesized silica. Standard catalytic activity tests were carried out on a bench-scale laboratory apparatus using a reaction mixture of a standard test. GHSV of 48,000 h􀀀1 was adopted based on the space velocity of a real NH3-SCR catalyst for diesel vehicles (100–550 C). All Cu-doped samples showed better NO conversion values than Fe-doped samples. Clinoptilolite catalysts were more active than those based on SBA-15. Maximum NO conversions of about 96% were observed for Cu-CLIN and Fe-CLIN at 350–400 C, respectively. Moreover, Fe-CLIN also showed higher stability in the presence of SO2 and water steam at 350 C. These results demonstrate the potential of metal-doped natural clinoptilolite to be used as cost-effective catalysts applied to the abatement of NOx emissions generated in automotive combustion processes.
Keywords: Aire - Contaminación; Combustibles fósiles; Nitrogen oxides emissions; SCR-NOx; Diesel engines; Natural zeolite; Clinoptilolite; SBA-15